Solid electrolytic capacitor and manufacturing method
The method of forming a solid electrolyte layer with conductive polymers and reducing sugars in solid electrolytic capacitors addresses the issue of high ESR, leading to improved stability and performance by stabilizing ESR changes.
Patent Information
- Application Number
- JP2023166469
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-27
- Publication Date
- 2025-04-09
AI Technical Summary
Solid electrolytic capacitors with high equivalent series resistance (ESR) experience heat generation, leading to conductive polymer degradation and reduced lifespan, limiting allowable ripple current and voltage smoothing capability.
A manufacturing method for solid electrolytic capacitors involves forming a solid electrolyte layer with a conductive polymer and reducing sugars or hydrolyzable non-reducing sugars, followed by an impregnation step with an electrolyte solution and a heating step to decompose the sugars, thereby stabilizing the ESR.
The approach results in a solid electrolytic capacitor with a low ESR change rate, enhancing its lifespan and performance by suppressing ESR increases even under high temperature conditions.
Smart Images

Figure 2025056931000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a solid electrolytic capacitor and a manufacturing method thereof. [Background technology]
[0002] An electrolytic capacitor has valve metals such as tantalum or aluminum as anode and cathode foils. The anode foil is enlarged by forming the valve metal into a sintered or etched foil, etc., and has a dielectric coating layer on the enlarged surface. An electrolyte is interposed between the anode foil and the cathode foil. The electrolyte is in close contact with the uneven surface of the anode foil and functions as a true cathode.
[0003] Capacitors are used in various applications. For example, in the field of power electronics, a power supply circuit converts the power of an AC power source into DC power using a converter circuit, and then converts the DC power into a desired AC power using an inverter circuit. In order to suppress and smooth the pulsation of the DC output from the converter circuit before inputting it to the inverter circuit, a decoupling capacitor is provided near the semiconductor switching element such as gallium nitride to ensure stable operation of the semiconductor switching element and remove noise. With the increasing power in the field of power electronics, there is a strong demand for capacitors with higher capacity.
[0004] In this regard, electrolytic capacitors have the advantage that the specific surface area can be increased by expanding the surface area of the anode foil, making it easier to obtain a large capacitance compared to other types of capacitors such as film capacitors. Electrolytic capacitors contain electrolyte in the form of an electrolytic solution. The contact area of the electrolyte with the dielectric film of the anode foil increases. This makes it easier to further increase the capacitance of the electrolytic capacitor.
[0005] In recent years, solid electrolytic capacitors that use a solid electrolyte with higher conductivity than the electrolyte have also become popular (see, for example, Patent Document 1). Solid electrolytic capacitors are small and have a large capacity, and use a solid electrolyte with higher conductivity than the electrolyte, making it possible to achieve a low equivalent series resistance (ESR). Known examples of solid electrolytes include manganese dioxide and 7,7,8,8-tetracyanoquinodimethane (TCNQ) complexes.
[0006] Known examples of solid electrolytes include manganese dioxide and 7,7,8,8-tetracyanoquinodimethane (TCNQ) complexes. In recent years, conductive polymers derived from monomers with π-conjugated double bonds, such as poly(3,4-ethylenedioxythiophene) (PEDOT), which has a slow reaction rate and excellent adhesion to dielectric films, have rapidly become popular as solid electrolytes. Conductive polymers use acid compounds such as polyanions as dopants, and have a partial structure within the monomer molecule that acts as a dopant, resulting in high conductivity.
[0007] In addition to having a low equivalent series resistance, solid electrolytic capacitors have the advantage of being long-lived, since there is no risk of the electrolyte drying up due to evaporation to the outside over time. However, so-called hybrid-type solid electrolytic capacitors that use both conductive polymers and electrolytes to provide a repair function for defects in the dielectric film and reduce leakage current in solid electrolytic capacitors are also becoming popular (see, for example, Patent Document 2). [Prior art documents] [Patent documents]
[0008] [Patent Document 1] JP 2011-60980 A [Patent Document 2] JP 2015-228424 A Summary of the Invention [Problem to be solved by the invention]
[0009] If a solid electrolytic capacitor has a high equivalent series resistance (ESR), it will generate heat, causing thermal degradation of the conductive polymer, and shortening the lifespan of the solid electrolytic capacitor. As a result, the solid electrolytic capacitor is affected by the equivalent series resistance, and the allowable ripple current is limited. When solid electrolytic capacitors are used in the voltage smoothing circuits of power converters, many solid electrolytic capacitors are connected in parallel to handle the ripple current. Therefore, there is a demand for solid electrolytic capacitors with a lower equivalent series resistance.
[0010] In addition, if the ESR of a solid electrolytic capacitor is high, a voltage drop occurs due to the ESR when the solid electrolytic capacitor is discharged, and a voltage rise occurs due to the ESR when the solid electrolytic capacitor is charged. In other words, the solid electrolytic capacitor causes voltage fluctuations. Therefore, a solid electrolytic capacitor with a high ESR has a low voltage smoothing ability.
[0011] The present invention has been proposed to solve the above problems, and an object of the present invention is to provide a solid electrolytic capacitor having a low rate of change in equivalent series resistance, and a manufacturing method thereof. [Means for solving the problem]
[0012] In order to solve the above problems, the method for manufacturing the solid electrolytic capacitor of this embodiment includes a solid electrolyte layer formation step of forming a solid electrolyte layer containing a conductive polymer between an anode body and a cathode body having a dielectric film, an impregnation step of impregnating a capacitor element having the anode body, the cathode body, and the solid electrolyte layer with an electrolyte solution containing reducing sugars or hydrolyzable non-reducing sugars, and a heating step of heating, after the impregnation step, until the reducing sugars or hydrolyzable sugars contained in the electrolyte solution are decomposed.
[0013] In addition, in order to solve the above-mentioned problems, the manufacturing method of the solid electrolytic capacitor of this embodiment includes a solid electrolyte layer formation step of forming a solid electrolyte layer containing a conductive polymer and a reducing sugar or a hydrolyzable non-reducing sugar between an anode body having a dielectric film and a cathode body, and a heating step of heating the solid electrolyte layer after the solid electrolyte layer formation step until the reducing sugar or hydrolyzable non-reducing sugar contained in the solid electrolyte layer is decomposed.
[0014] The heating step may be a period during which the solid electrolytic capacitor mounted on a circuit and in use is exposed to a high-temperature environment or generates heat.
[0015] The reducing sugar or hydrolyzable non-reducing sugar may be one or more selected from the group consisting of maltose, lactose, isomaltulose, melibiose, raffinose and melezitose.
[0016] In addition, in order to solve the above problems, the solid electrolytic capacitor of this embodiment includes an anode body having a dielectric film, a solid electrolyte layer interposed between the anode body and the cathode body and containing a conductive polymer, or an electrolyte layer containing both the solid electrolyte layer and an electrolytic solution, and a reducing sugar or a hydrolyzable non-reducing sugar contained in the electrolyte layer.
[0017] The reducing sugar or hydrolyzable non-reducing sugar may be one or more selected from the group consisting of maltose, lactose, isomaltulose, melibiose, raffinose and melezitose.
[0018] In order to solve the above problems, the solid electrolytic capacitor of the present embodiment includes an anode body having a dielectric film, a solid electrolyte layer interposed between the anode body and the cathode body and containing a conductive polymer, or an electrolyte layer containing both the solid electrolyte layer and an electrolytic solution, and a decomposition product derived from a reducing sugar or a hydrolyzable non-reducing sugar that is contained in the electrolyte layer. Effect of the Invention
[0019] According to the present invention, the solid electrolytic capacitor has a low ESR change rate. [Brief description of the drawings]
[0020] [Figure 1] 1 is a graph showing the relationship between the elapsed time and the rate of change in ESR when a load is applied at 150° C. when reducing sugar or hydrolyzable non-reducing sugar is contained in a solid electrolyte layer. [Diagram 2] 1 is a graph showing the relationship between the elapsed time under load at 150° C. and the rate of change in ESR when reducing sugar or hydrolyzable non-reducing sugar is contained in the electrolyte. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0021] Hereinafter, a solid electrolytic capacitor according to an embodiment will be described, however, the present invention is not limited to the embodiment described below.
[0022] (Solid electrolytic capacitor) A solid electrolytic capacitor is a passive device that obtains capacitance by the dielectric polarization of a dielectric film and stores and discharges electric charge. The solid electrolytic capacitor includes a capacitor element. The capacitor element includes an anode body, a cathode body, and an electrolyte layer. A dielectric film is formed on the anode body.
[0023] The anode body and the cathode body face each other with an electrolyte layer therebetween. The electrolyte layer is interposed between the dielectric film of the anode body and the cathode body, and functions as a true cathode in close contact with the dielectric film of the anode body. The electrolyte layer is a solid electrolyte layer containing a conductive polymer. The electrolyte layer may be formed of a solid electrolyte layer and an electrolyte solution. The electrolyte solution is impregnated into the voids of the capacitor element in which the solid electrolyte layer is formed. The electrolyte, i.e., the solid electrolyte layer, the electrolyte solution, or both, contains a reducing sugar or a hydrolyzable non-reducing sugar.
[0024] A separator may be interposed between the anode body and the cathode body. The separator holds the solid electrolyte layer and the electrolytic solution. The separator also prevents short-circuiting between the anode body and the cathode body. When the electrolyte layer is formed of a solid electrolyte layer, the solid electrolyte layer retains its shape by itself, and the solid electrolyte layer separates the anode body and the cathode body, the separator can be omitted from the configuration of the solid electrolytic capacitor.
[0025] Such solid electrolytic capacitors are classified into, for example, a laminated type, a wound type, and a flat type. In the laminated type, anode bodies and cathode bodies are alternately laminated with a separator sandwiched therebetween. In the wound type, the anode bodies and cathode bodies are wound with a separator sandwiched therebetween. In the flat type, a solid electrolyte layer and a cathode body are laminated on an anode body.
[0026] (Manufacturing method) This solid electrolytic capacitor is manufactured through an anode processing step for processing an anode body, a cathode processing step for processing a cathode body, a solid electrolyte layer forming step for forming a solid electrolyte layer, an impregnation step for impregnating an electrolyte solution, and a final assembly step for sealing the capacitor element in an exterior case. In addition, if the solid electrolytic capacitor is a wound type, a winding step is performed before the solid electrolyte layer forming step, in which the anode body and the cathode body are wound with a separator interposed therebetween.
[0027] During use, when the solid electrolytic capacitor is heated, the reducing sugar or hydrolyzable non-reducing sugar decomposes. This decomposition reaction may occur during the manufacturing process in the capacitor production facility by including a heating step in the manufacturing process.
[0028] The order of these steps can be freely rearranged as much as possible, and parallel processing is also possible. Furthermore, one step may include a plurality of substeps, some of which may be carried out during another step, or may be incorporated between one substep of another step and the next substep.
[0029] (Anode body and anode processing process) The anode body is a foil made of a valve metal, for example, an anode foil. The valve metal is aluminum, tantalum, niobium, niobium oxide, titanium, hafnium, zirconium, zinc, tungsten, bismuth, antimony, etc. The purity of the valve metal is preferably 99.9% or more for the anode foil, and may contain silicon, iron, copper, magnesium, zinc, etc.
[0030] In the anode processing step, a base material for the anode foil is prepared. The base material for the anode may be formed by stretching a valve metal or the like, or may be formed by sintering a powder of the valve metal. In a wound electrolytic capacitor, the anode body has a long strip shape, while in a laminated and flat electrolytic capacitor, the anode body is a flat plate.
[0031] The anode body has a surface-expanding layer on one or both sides. This surface-expanding layer is formed by subjecting the base material of the anode foil to a surface-expanding treatment. The surface-expanding layer can be an etching layer formed by etching the foil, a sintered layer formed by sintering valve metal powder, or a vapor-deposited layer formed by vapor-depositing valve metal particles onto the foil. That is, the surface-expanding layer has a porous structure and is composed of tunnel-like pits that are holes dug in the thickness direction of the foil, spongy pits that make the surface-expanding layer into a sponge-like layer with fine voids that are connected together in a space, or voids between densely packed powder or particles.
[0032] The dielectric film is formed on one or both sides of the anode body on which the surface-expanding layer is formed. The dielectric film is formed on the surface layer of the surface-expanding layer along the irregularities of the surface-expanding layer. The dielectric film is typically an oxide film formed on the surface layer of the anode body, and if the anode body is made of aluminum, it is an aluminum oxide layer obtained by oxidizing the surface of the surface-expanding layer.
[0033] In the chemical conversion treatment for forming the dielectric film, a voltage corresponding to a desired withstand voltage is applied to the anode body in the chemical conversion solution. To obtain a withstand voltage of 1 V, it is preferable to form a dielectric film having a thickness of 1.1 to 1.5 nm. The chemical conversion solution is a solution that does not contain halogen ions, and is, for example, a phosphoric acid-based chemical conversion solution such as ammonium dihydrogen phosphate, a boric acid-based chemical conversion solution such as ammonium borate, or an adipic acid-based chemical conversion solution such as ammonium adipate.
[0034] (Cathode body and cathode processing process) In the case of a wound-type electrolytic capacitor, the cathode body is preferably a base material made of a valve metal and stretched in the cathode processing step. This foil is called a cathode foil. The purity of the cathode body is preferably 99% or more. The cathode body has a surface-expanding layer formed thereon, as with the anode body. The surface-expanding layer of the cathode body may be formed by a surface-expanding treatment, as with the anode body. A plain foil without a surface-expanding layer may be used as the cathode body. The cathode body may have a natural oxide film or a thin oxide film of about 1 to 10 Vfs formed by chemical conversion treatment. The natural oxide film is formed by the reaction of the cathode body with oxygen in the air.
[0035] Further, the cathode body may be provided with a conductive layer. The conductive layer may mainly contain an inorganic substance or an inorganic compound. Examples of the inorganic substance or inorganic compound include titanium, zirconium, tantalum, niobium, nitrides or carbides thereof, aluminum carbide, carbon materials, and composites or mixtures thereof. Examples of the carbon material include graphite, carbon black, activated carbon, carbon nanohorns, fibrous carbon, or mixtures thereof. Methods for forming the carbon layer on the cathode foil include vacuum deposition, sputtering, ion plating, CVD, coating, electrolytic plating, and electroless plating. After laminating the conductive layer and the cathode foil, it is preferable to press them together by pressing.
[0036] In the case of a laminated solid electrolytic capacitor, the cathode body is preferably a laminate of a metal layer and a carbon layer. The carbon layer of the cathode body is disposed facing the anode body. The carbon layer is formed in a paste form, and after the solid electrolyte layer forming step of forming the solid electrolyte layer on the anode body, the carbon layer is applied on the solid electrolyte layer by a screen printer or the like, and then cured by heating. The metal layer is, for example, a silver layer, and is formed in a paste form, and then applied on the carbon layer, and then cured by heating.
[0037] In the case of a stacked solid electrolytic capacitor, an insulating resist layer is printed and dried before forming a cathode body and a solid electrolyte layer. The insulating resist layer includes an area that will become an anode terminal, but excludes an area that will become an anode. That is, the insulating resist layer is printed so that a solid electrolyte layer and a cathode body are not formed in an area that will become an anode terminal. The insulating resist layer is peeled off after forming the cathode body.
[0038] (Solid electrolyte layer and formation process) The solid electrolyte layer contains reducing sugars together with the conductive polymer. Glucose is generated from the reducing sugars. Glucose has a hemiacetal structure. When glucose is heated under acidic or alkaline conditions, an acidic or alkaline compound is generated depending on the pH. The acidic compounds generated include gluconic acid, glucuronic acid, levulinic acid, lactic acid, formic acid, etc., or a combination of these. The alkaline compounds generated include glucosamine, 5-hydroxymethylfurfural, 2,6-deoxyfructosazine, mannosamine, etc., or a combination of these. These decomposition products derived from reducing sugars act to suppress the pH change of the electrolyte solution during high-temperature storage, suppress the dedoping of the conductive polymer, and maintain the conductivity of the conductive polymer. Therefore, when the solid electrolytic capacitor is unintentionally exposed to a high-temperature environment, the decomposition reaction of the reducing sugar occurs, suppressing the increase in the ESR of the solid electrolytic capacitor.
[0039] The solid electrolyte layer may contain a hydrolyzable non-reducing sugar instead of or together with the reducing sugar. The hydrolyzable non-reducing sugar has an ether bond in its molecular structure and becomes a reducing sugar by hydrolysis. The non-reducing sugar is hydrolyzed to produce a reducing sugar, which is decomposed by heating under acidic or alkaline conditions, and the product inhibits dedoping of the conductive polymer.
[0040] However, acidic compounds such as gluconic acid, glucuronic acid, levulinic acid, lactic acid, and formic acid act to lower the pH inside the solid electrolytic capacitor. Therefore, if these acidic compounds are present in a situation where there is no factor that increases the pH, such as a high-temperature environment, they may dissolve the anode and cathode bodies. In addition, if alkaline compounds such as glucosamine, 5-hydroxymethylfurfural, 2,6-deoxyfructosazine, and mannosamine are present in a situation other than a high-temperature environment, they may actually accelerate the undoping of the conductive polymer.
[0041] However, the solid electrolyte layer does not directly contain these acidic or alkaline compounds, but contains reducing sugars or hydrolyzable non-reducing sugars that are decomposed into these acidic or alkaline compounds when placed in a high-temperature environment where the pH of the electrolyte changes. Therefore, the risk of these acidic or alkaline compounds dissolving the anode body and cathode body is reduced, and the risk of accelerating undoping is also reduced. On the other hand, when the solid electrolytic capacitor is heated, when it is mounted in a circuit and used in a high-temperature environment, or when the solid electrolytic capacitor is mounted in a circuit and used and generates heat, these acidic or alkaline compounds are generated, suppressing an increase in the ESR of the solid electrolytic capacitor.
[0042] In addition, when reducing sugars such as glucose or other monosaccharides are directly added to the conductive polymer solution or the electrolyte, the decomposition reaction rate is expected to be fast, and even if they are added during the manufacture of the solid electrolytic capacitor, the decomposition reaction is likely to proceed after the product is shipped, and there is a risk that they will not contribute to dedoping when the product is exposed to a high-temperature environment during use. However, since this solid electrolyte layer contains reducing sugars from which glucose is generated or non-reducing sugars that can be hydrolyzed, the progression to acidic or alkaline compounds is delayed by the amount of the process of generating glucose. Therefore, there is a high possibility that they will contribute to dedoping when the product is exposed to a high-temperature environment during use.
[0043] Such reducing sugars or hydrolyzable non-reducing sugars are, for example, one or more selected from the group consisting of maltose, lactose, isomaltulose, melibiose, raffinose and melezitose. Raffinose is decomposed by hydrolysis into reducing sugars melibiose and fructose, and melibiose is decomposed by hydrolysis into reducing sugars galactose and glucose. Melezitose is decomposed by hydrolysis into reducing sugars sucrose and glucose, and sucrose is decomposed by hydrolysis into reducing sugars glucose and fructose.
[0044] Reducing sugars have a short reaction process to generate products that inhibit de-doping. Hydrolyzable non-reducing sugars have a long reaction process to generate products that inhibit de-doping. Therefore, when both reducing sugars and hydrolyzable non-reducing sugars are contained in a solid electrolytic capacitor, the increase in ESR is gradually suppressed over a long period of time.
[0045] The conductive polymer in which dedoping is suppressed by a reducing sugar or a hydrolyzable non-reducing sugar is not particularly limited as long as it is a conjugated polymer doped with an external dopant molecule. The conjugated polymer is obtained by chemical oxidative polymerization or electrolytic oxidative polymerization of a monomer having a π-conjugated double bond or a derivative thereof. The dopant or external dopant molecule is an acceptor that easily accepts electrons into the conjugated polymer, or a donor that easily gives electrons to the conjugated polymer, and this allows the conductive polymer to exhibit high conductivity.
[0046] The conjugated polymer may be any known polymer without any particular limitation. For example, polypyrrole, polythiophene, polyfuran, polyaniline, polyacetylene, polyphenylene, polyphenylenevinylene, polyacene, polythiophenevinylene, etc. These conjugated polymers may be used alone, or in combination of two or more kinds, or may be a copolymer of two or more kinds of monomers.
[0047] Among the above conjugated polymers, preferred are conjugated polymers obtained by polymerizing thiophene or its derivatives, and preferred are conjugated polymers obtained by polymerizing 3,4-ethylenedioxythiophene (i.e., 2,3-dihydrothieno[3,4-b][1,4]dioxine), 3-alkylthiophene, 3-alkoxythiophene, 3-alkyl-4-alkoxythiophene, 3,4-alkylthiophene, 3,4-alkoxythiophene, or derivatives thereof. As the thiophene derivative, a compound selected from thiophenes having substituents at the 3rd and 4th positions is preferred, and the substituents at the 3rd and 4th positions of the thiophene ring may form a ring together with the carbons at the 3rd and 4th positions. The number of carbon atoms of the alkyl group or alkoxy group is preferably 1 to 16.
[0048] In particular, a polymer of 3,4-ethylenedioxythiophene called EDOT, that is, poly(3,4-ethylenedioxythiophene) called PEDOT, is preferred. A substituent may be added to 3,4-ethylenedioxythiophene. For example, an alkylated ethylenedioxythiophene having an alkyl group having 1 to 5 carbon atoms added as a substituent may be used. Examples of alkylated ethylenedioxythiophene include methylated ethylenedioxythiophene (i.e., 2-methyl-2,3-dihydro-thieno[3,4-b][1,4]dioxine), ethylated ethylenedioxythiophene (i.e., 2-ethyl-2,3-dihydro-thieno[3,4-b][1,4]dioxine), butylated ethylenedioxythiophene (i.e., 2-butyl-2,3-dihydro-thieno[3,4-b][1,4]dioxine), and 2-alkyl-3,4-ethylenedioxythiophene.
[0049] The dopant may be any known dopant without any particular limitation. The dopant may be used alone or in combination of two or more. A polymer or monomer may also be used. For example, the dopant may be an inorganic acid such as a polyanion, boric acid, nitric acid, or phosphoric acid, or an organic acid such as acetic acid, oxalic acid, citric acid, tartaric acid, squaric acid, rhodizonic acid, croconic acid, salicylic acid, p-toluenesulfonic acid, 1,2-dihydroxy-3,5-benzenedisulfonic acid, methanesulfonic acid, trifluoromethanesulfonic acid, borodisalicylic acid, bisoxalate borate acid, sulfonylimide acid, dodecylbenzenesulfonic acid, propylnaphthalenesulfonic acid, or butylnaphthalenesulfonic acid.
[0050] Examples of the polyanion include substituted or unsubstituted polyalkylene, substituted or unsubstituted polyalkenylene, substituted or unsubstituted polyimide, substituted or unsubstituted polyamide, and substituted or unsubstituted polyester, and include polymers consisting of only structural units having an anionic group, and polymers consisting of structural units having an anionic group and structural units not having an anionic group.Specific examples of the polyanion include polyvinyl sulfonic acid, polystyrene sulfonic acid, polyallyl sulfonic acid, polyacryl sulfonic acid, polymethacryl sulfonic acid, poly(2-acrylamido-2-methylpropane sulfonic acid), polyisoprene sulfonic acid, polyacrylic acid, polymethacrylic acid, and polymaleic acid.
[0051] An example of the conductive polymer is poly(3,4-ethylenedioxythiophene) doped with polystyrenesulfonic acid, and hereinafter this conductive polymer is referred to as PEDOT:PSS.
[0052] In the solid electrolyte layer forming process, a conductive polymer liquid can be used. The conductive polymer liquid is a dispersion or solution in which a conductive polymer is dispersed or dissolved. The dispersion medium or solvent of the conductive polymer liquid is water or a mixture of water and an organic solvent. The conductive polymer liquid is prepared by adding water in which a reducing sugar or a hydrolyzable non-reducing sugar is dissolved, or a mixture of water and an organic solvent, to the dispersion or solution of the conductive polymer. Suitable examples of the organic solvent include polar solvents, alcohols, esters, hydrocarbons, carbonate compounds, ether compounds, chain ethers, heterocyclic compounds, and nitrile compounds.
[0053] Examples of polar solvents include N-methyl-2-pyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide, and dimethyl sulfoxide. Examples of alcohols include methanol, ethanol, propanol, and butanol. Examples of esters include ethyl acetate, propyl acetate, and butyl acetate. Examples of hydrocarbons include hexane, heptane, benzene, toluene, and xylene. Examples of carbonate compounds include ethylene carbonate and propylene carbonate. Examples of ether compounds include dioxane and diethyl ether. Examples of chain ethers include ethylene glycol dialkyl ether, propylene glycol dialkyl ether, polyethylene glycol dialkyl ether, and polypropylene glycol dialkyl ether. Examples of heterocyclic compounds include 3-methyl-2-oxazolidinone. Examples of nitrile compounds include acetonitrile, glutarodinitrile, methoxyacetonitrile, propionitrile, and benzonitrile.
[0054] The conductive polymer liquid may contain a polyhydric alcohol in addition to the dispersion medium or solvent. Examples of the polyhydric alcohol include sorbitol, ethylene glycol, diethylene glycol, triethylene glycol, polyoxyethylene glycol, glycerin, polyoxyethyleneglycerin, xylitol, erythritol, mannitol, dipentaerythritol, pentaerythritol, and combinations of two or more of these. Since the polyhydric alcohol has a high boiling point, it remains in the conductive polymer layer even after the drying process. The polyhydric alcohol changes the higher-order structure of the conductive polymer and reorients the crystal structure of the polymer chain. Therefore, the polyhydric alcohol improves the carrier mobility, improves the electrical conductivity of the conductive polymer, and reduces the ESR of the solid electrolytic capacitor.
[0055] The pH of the conductive polymer liquid is adjusted from the viewpoint of improving the acidity so that the anode body, the cathode body, and the separator do not dissolve, and additives may be added as necessary. If the pH is in the range of 2 to 9, dissolution of the separator, the anode body, and the cathode body is suppressed. Examples of the pH adjuster include ammonia water, sodium hydroxide, primary amines, secondary amines, and tertiary amines. Examples of the additives include organic binders, surfactants, dispersants, antifoaming agents, coupling agents, antioxidants, and ultraviolet absorbers.
[0056] In the solid electrolyte layer forming step, the capacitor element is immersed in the conductive polymer liquid to impregnate the capacitor element with the conductive polymer liquid. Alternatively, after printing an insulating resist layer on the region that will become the anode terminal, the conductive polymer liquid is applied to the anode body by drop application, spray application, or the like. The conductive polymer liquid may be immersed or applied once or multiple times. The wound body may be placed in a reduced pressure environment to be impregnated with the conductive polymer liquid.
[0057] After the immersion, the solvent of the conductive polymer solution is removed by a drying process. The temperature environment in the drying process is, for example, 40°C to 200°C, and the drying time is, for example, in the range of 3 minutes to 180 minutes. Drying processes at various temperatures and for various times may be repeated multiple times. Drying may be performed in a reduced pressure environment, for example, by reducing the pressure to 5 kPa to 100 kPa.
[0058] The heating for decomposing the reducing sugar or hydrolyzable non-reducing sugar utilizes the temperature rise of the solid electrolytic capacitor during use. That is, the manufacturing process of the solid electrolytic capacitor includes intentional or unintentional heating during use. Also, the heating step may be performed after the reducing sugar or hydrolyzable non-reducing sugar is incorporated into the solid electrolytic capacitor in the capacitor production factory. That is, the heating step may be performed after the solid electrolyte layer formation step or after the final assembly step. Furthermore, the solid electrolytic capacitor may be used without performing this heating step, and the temperature of the usage environment or the heat generated by the solid electrolytic capacitor during use may be used instead of the heating step.
[0059] In the heating step, in order to decompose reducing sugar or hydrolyzable non-reducing sugar, the internal temperature of the solid electrolytic capacitor is raised to 85°C or higher, and this internal temperature is maintained for 1 hour or more. In order to decompose reducing sugar or hydrolyzable non-reducing sugar, an acidic pH of 3 to 6 or an alkaline pH of 8 to 9 is preferable, and the conductive polymer liquid is adjusted with a pH adjuster. Examples of pH adjusters for the conductive polymer liquid include ammonia water, sodium hydroxide, primary amines, secondary amines, and tertiary amines. The conductive polymer liquid may also be neutral at pH 7.
[0060] (Electrolyte and impregnation process) When an electrolyte solution is used in addition to the solid electrolyte layer, reducing sugar or hydrolyzable non-reducing sugar may be added to the electrolyte solution. In order to decompose reducing sugar or hydrolyzable non-reducing sugar, the pH of the electrolyte solution is adjusted to an acidic pH of 3 to 6 or an alkaline pH of 8 to 9. Examples of pH adjusters for the electrolyte solution include ammonia water, sodium hydroxide, primary amines, secondary amines, tertiary amines, and quaternary amidinium. The electrolyte solution may also be neutral at pH 7.
[0061] The electrolyte is a solution in which a solute is added to a solvent. The solute is an organic acid or its salt, an inorganic acid or its salt, or a composite compound of an organic acid and an inorganic acid or its salt, and is an ion-dissociable salt that dissociates into an anion component and a cation component. The solvent may be used alone or in combination of two or more kinds.
[0062] Examples of organic acids that serve as anion components as solutes include carboxylic acids such as oxalic acid, succinic acid, glutaric acid, pimelic acid, suberic acid, sebacic acid, phthalic acid, isophthalic acid, terephthalic acid, maleic acid, adipic acid, benzoic acid, toluic acid, enanthic acid, malonic acid, 1,6-decanedicarboxylic acid, 1,7-octanedicarboxylic acid, azelaic acid, resorcylic acid, phloroglucic acid, gallic acid, gentisic acid, protocatechuic acid, pyrocatechuic acid, trimellitic acid, and pyromellitic acid, as well as phenols and sulfonic acids. Examples of inorganic acids include boric acid, phosphoric acid, phosphorous acid, hypophosphorous acid, carbonic acid, and silicic acid. Examples of composite compounds of organic acids and inorganic acids include borodisalicylic acid, borodioxalic acid, borodiglycolic acid, borodimalonic acid, borodisuccinic acid, borodiadipic acid, borodiazelaic acid, borodibenzoic acid, borodimaleic acid, borodilactic acid, borodimalic acid, boroditartaric acid, borodicitric acid, borodiphthalic acid, borodi(2-hydroxy)isobutyric acid, borodiresorcylic acid, borodimethylsalicylic acid, borodinaphthoic acid, borodimandelic acid, and borodi(3-hydroxy)propionic acid.
[0063] In addition, examples of at least one salt of an organic acid, an inorganic acid, and a complex compound of an organic acid and an inorganic acid include ammonium salt, quaternary ammonium salt, quaternary amidinium salt, amine salt, sodium salt, potassium salt, etc. Examples of quaternary ammonium ions of quaternary ammonium salts include tetramethylammonium, triethylmethylammonium, tetraethylammonium, etc. Examples of quaternary amidinium salts include ethyldimethylimidazolinium, tetramethylimidazolinium, etc. Examples of amine salts include salts of primary amines, secondary amines, and tertiary amines. Examples of primary amines include methylamine, ethylamine, propylamine, etc., examples of secondary amines include dimethylamine, diethylamine, ethylmethylamine, dibutylamine, etc., and examples of tertiary amines include trimethylamine, triethylamine, tributylamine, ethyldimethylamine, ethyldiisopropylamine, etc.
[0064] The solvent may be either a protic polar solvent or an aprotic polar solvent. Representative examples of the protic polar solvent include monohydric alcohols, polyhydric alcohols, and oxyalcohol compounds. Representative examples of the aprotic polar solvent include sulfones, amides, lactones, cyclic amides, nitriles, and sulfoxides.
[0065] Furthermore, in addition to the reducing sugar or hydrolyzable non-reducing sugar, additives may be added to the electrolyte. Examples of additives include complex compounds of boric acid and polysaccharides (mannite, sorbitol, etc.), complex compounds of boric acid and polyhydric alcohols, borate esters, nitro compounds, phosphate esters, colloidal silica, and high-boiling point solvents such as polyhydric alcohols. These may be used alone or in combination of two or more.
[0066] The electrolyte is impregnated into the capacitor element in an impregnation step. The capacitor element is immersed in the electrolyte, and may be subjected to a depressurization treatment or a pressurization treatment as necessary. The electrolyte impregnation step may be repeated multiple times. For example, the inside of the capacitor element may be depressurized, and the electrolyte may be injected into the inside of the capacitor element while pressurizing the electrolyte.
[0067] (Separator and winding process) In a wound solid electrolytic capacitor, when a separator is interposed between an anode body and a cathode body, the separator is overlapped so that one end of the separator protrudes beyond one end of the anode body and the cathode body. The protruding separator is wound first so that the core of the wound body is aligned with the short sides of the anode body and the cathode body to create a winding core. Then, the winding core is used as a winding axis to roll the long sides of the anode body and the cathode body.
[0068] The separator may be made of cellulose such as kraft, Manila hemp, esparto, hemp, rayon, or the like, or mixed papers thereof; polyester-based resins such as polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, and derivatives thereof; polytetrafluoroethylene-based resins, polyvinylidene fluoride-based resins, vinylon-based resins, polyamide-based resins such as aliphatic polyamides, semi-aromatic polyamides, and fully aromatic polyamides; polyimide-based resins, polyethylene resins, polypropylene resins, trimethylpentene resins, polyphenylene sulfide resins, acrylic resins, and polyvinyl alcohol resins; and the like, and these resins may be used alone or in combination.
[0069] After winding, a repair formation process may be provided to repair the bare metal portion of the valve metal exposed when the anode body and the cathode body are cut to a desired width, and defects in the anode body and the cathode body caused by physical stress such as winding. In the repair formation process, the capacitor element is immersed in a formation liquid and a voltage is applied. As the formation liquid, a phosphoric acid-based formation liquid such as ammonium dihydrogen phosphate, a boric acid-based formation liquid such as ammonium borate, an adipic acid-based formation liquid such as ammonium adipate, or a formation liquid in which boric acid and a dicarboxylic acid such as citric acid are mixed is used. The voltage is preferably set to, for example, 0.1 to 1.2 times the formation voltage. In addition, as a method of applying a voltage during repair formation, a method of applying a constant voltage from the start of repair formation, or a method of increasing the applied voltage stepwise at regular intervals, etc. are appropriately selected.
[0070] (Outer case and final assembly process) In a wound-type solid electrolytic capacitor, the capacitor element is housed in an exterior case that is bottomed at one end and open at the other end, and the capacitor element is sealed in the exterior case with a sealing body. The sealing body is crimped from the outside of the exterior case. In a stacked-type solid electrolytic capacitor, the exterior is omitted and the capacitor element is covered with a laminate film, for example. Alternatively, the capacitor element is sealed by molding, dip coating, or printing a resin such as a heat-resistant resin or an insulating resin. After sealing the capacitor element, the electrolytic capacitor is subjected to an aging process to complete the production. In the aging process, a DC voltage equal to or higher than the chemical conversion voltage is applied to the electrolytic capacitor to repair defects in the dielectric oxide film layer, etc. EXAMPLES
[0071] The solid electrolytic capacitors of the examples will be described in more detail below, but the present invention is not limited to the examples described below.
[0072] (Examples 1 to 4) Solid electrolytic capacitors were produced in Examples 1 to 4 and Comparative Examples 1 and 2. In the solid electrolytic capacitors in Examples 1 to 4, reducing sugar or hydrolyzable non-reducing sugar was contained in the solid electrolyte layer.
[0073] In Examples 1 to 4 and Comparative Examples 1 and 2, a common anode body and a cathode body were used. The anode body was an aluminum anode foil, and the cathode body was an aluminum cathode foil. The anode foil was etched to form a surface-enlarged layer consisting of spongy etching pits. The anode foil was then chemically treated to form a dielectric film. During the chemical treatment, the anode foil was immersed in an aqueous solution of ammonium adipate at a liquid temperature of 85°C, and a constant current of 2 mA was passed through it. After the voltage reached 63 V, a constant voltage of 63 V was applied.
[0074] The cathode foil was etched to form a surface-expanding layer consisting of spongy etching pits. The cathode foil was then chemically treated to form a dielectric film. During the chemical treatment, the cathode foil was immersed in an aqueous solution of ammonium adipate at a liquid temperature of 85°C, and a constant current of 2 mA was passed through it. After the voltage reached 3 V, a constant voltage of 3 V was applied. A manila paper separator was prepared, and the anode foil and cathode foil were stacked with the separator in between and wound to create a wound body. The capacitor element had a diameter of 8 mm and a length of 10 mm, a theoretical capacitance of 150 μF, and a rated voltage of 35 WV.
[0075] By impregnating this capacitor element with a conductive polymer liquid, conductive polymer particles were attached to the dielectric film of the anode foil, the cathode foil, and the inside of the separator. The conductive polymer liquid was prepared as follows. PEDOT:PSS was used as the conductive polymer. PEDOT:PSS was added to an aqueous dispersion medium to prepare a conductive polymer dispersion with a conductive polymer concentration of 2.6 wt%. 25 wt% ethylene glycol and 10 wt% water were added to the aqueous dispersion. Furthermore, the pH of the dispersion was adjusted to 4 with ammonia. 5 wt% sugar was added to this dispersion, and it was subjected to ultrasonic dispersion treatment for 5 minutes.
[0076] The conductive polymer solution was impregnated for 3 minutes in a reduced pressure environment of 10 kPa. After impregnation with the conductive polymer solution, the capacitor element was dried for 10 minutes in a temperature environment of 60°C, and further dried at 120°C or 150°C. In this way, a capacitor element was produced in which a solid electrolyte layer was formed between the anode foil and the cathode foil.
[0077] In Example 1, isomaltulose, a reducing sugar, was added to the conductive polymer liquid, and isomaltulose was contained in the solid electrolyte layer. In Example 2, melibiose, a reducing sugar, was added to the conductive polymer liquid, and melibiose was contained in the solid electrolyte layer. In Example 3, raffinose, a hydrolyzable non-reducing sugar, was added to the conductive polymer liquid, and raffinose was contained in the solid electrolyte layer. In Example 4, melezitose, a hydrolyzable non-reducing sugar, was added to the conductive polymer liquid, and melezitose was contained in the solid electrolyte layer. No sugars were added to the conductive polymer liquid of Comparative Example 1, and no sugars were contained in the solid electrolyte layer of Comparative Example 1. In Comparative Example 2, sorbitol, a non-reducing sugar that is not hydrolyzed, was added to the conductive polymer liquid, and sorbitol was contained in the solid electrolyte layer.
[0078] After the solid electrolyte layer formation process, the process moved to the impregnation process, where the capacitor element was impregnated with an electrolyte. The solvent for the electrolyte was ethylene glycol, and the solute for the electrolyte was ammonium azelaate at 1 wt% of the total electrolyte. The electrolyte was impregnated into the capacitor element for 3 minutes in an environment reduced in pressure to 10 kPa. The capacitor element was housed in an aluminum case with one end closed and the other end open. A rubber seal was inserted into the opening of the aluminum case, and the outside of the aluminum case was crimped to seal the capacitor element.
[0079] After the final assembly process, the solid electrolytic capacitors of Examples 1 to 4 and Comparative Examples 1 and 2 were subjected to a direct current voltage of 35 V and left in a temperature environment of 150° C.
[0080] (ESR test part 1) The ESR of the solid electrolytic capacitors of Examples 1 to 4 and Comparative Examples 1 and 2 was measured. The ESR was measured at an initial stage immediately before entering the heating process, 244 hours after entering the heating process, and 478 hours after entering the heating process. The ESR was measured using an LCR meter (Agilent ZM2376, manufactured by NF Corporation). The ambient temperature during the measurement was 25°C, the DC bias was 1.5V, the AC current level was a sine wave of 1.0Vrms, and the measurement frequency was 100kHz.
[0081] Using the initial ESR as the reference value, the rate of change in ESR after 244 hours and after 478 hours were calculated from the measurement results and are shown in Table 1 below. Based on Table 1 above, the relationship between the elapsed time when a load was applied at 150°C and the rate of change in ESR is shown in the graph in Figure 1. (Table 1) TIFF2025056931000002.tif56168
[0082] As shown in Table 1 and Figure 1, Comparative Example 1, which does not contain sugars, has an ESR that is more than three times higher than the initial ESR in an environment of 150°C. Even Comparative Example 2, which contains sorbitol, a non-reducing sugar that does not hydrolyze, has an ESR that is about 2.5 times higher than the initial ESR in an environment of 150°C. In contrast, Examples 1 to 4, which contain reducing sugars or hydrolyzable non-reducing sugars, have ESRs that are within the range of 1.1 to 1.5 times higher than the initial ESR even after long periods of exposure to an environment of 150°C.
[0083] In this way, it was confirmed that the increase in ESR of the solid electrolytic capacitor can be suppressed by forming a solid electrolyte layer using a conductive polymer liquid containing a conductive polymer and a reducing sugar or a hydrolyzable non-reducing sugar, and heating the capacitor element after the solid electrolyte layer formation process until the reducing sugar or hydrolyzable non-reducing sugar decomposes.
[0084] (Examples 5-10) Solid electrolytic capacitors were produced in Examples 5 to 10 and Comparative Examples 3 and 4. In the solid electrolytic capacitors in Examples 5 to 10, reducing sugar or hydrolyzable non-reducing sugar was contained in the electrolyte.
[0085] In Examples 5 to 10 and Comparative Examples 3 and 4, the same anode and cathode bodies as in Examples 1 to 4 were used. The solid electrolyte layer formation process was the same as in Examples 1 to 4, except that the conductive polymer solution did not contain reducing sugar or hydrolyzable non-reducing sugar, and the amount of water added together with 25 wt% ethylene glycol was 10 wt%.
[0086] After the solid electrolyte layer formation process, the impregnation process was carried out, in which the capacitor element was impregnated with an electrolyte. The solvent for the electrolyte was ethylene glycol, the solute for the electrolyte was ammonium azelaate at 1 wt% of the total electrolyte, and 9.1 wt% of sugars was added to the total electrolyte.
[0087] In Example 5, maltose, a reducing sugar, was added to the electrolyte. In Example 6, lactose, a reducing sugar, was added to the electrolyte. In Example 7, isomaltulose, a reducing sugar, was added to the electrolyte. In Example 8, melibiose, a reducing sugar, was added to the electrolyte. In Example 9, raffinose, a hydrolyzable non-reducing sugar, was added to the electrolyte. In Example 10, melezitose, a hydrolyzable non-reducing sugar, was added to the electrolyte. No sugars were added to the electrolyte in Comparative Example 3, and no sugars were contained in the solid electrolyte layer in Comparative Example 3. In Comparative Example 4, sorbitol, a non-reducing sugar that does not hydrolyze, was added to the electrolyte.
[0088] The capacitor element was impregnated with this electrolyte for 3 minutes under a reduced pressure of 10 kPa. The capacitor element was housed in an aluminum case with one end closed and the other end open. A rubber seal was inserted into the opening of the aluminum case, and the outside of the aluminum case was crimped to seal the capacitor element.
[0089] After the final assembly process, the solid electrolytic capacitors of Examples 5 to 10 and Comparative Examples 3 and 4 were subjected to a direct current voltage of 35 V and left in a temperature environment of 150° C.
[0090] (ESR test part 2) The ESR of the solid electrolytic capacitors of Examples 5 to 10 and Comparative Examples 3 and 4 was measured. The ESR was measured at an initial stage immediately before entering the heating process, 303 hours after entering the heating process, and 509 hours after entering the heating process. The ESR was measured using an LCR meter (Agilent ZM2376, manufactured by NF Corporation). The ambient temperature during the measurement was 25°C, the DC bias was 1.5V, the AC current level was a sine wave of 1.0Vrms, and the measurement frequency was 100kHz.
[0091] Using the initial ESR as the reference value, the ESR change rate after 303 hours and after 509 hours were calculated from the measurement results and are shown in Table 2 below. Based on Table 2 above, the relationship between the elapsed time when a load was applied at 150°C and the ESR change rate is shown in the graph of Figure 2. (Table 2) TIFF2025056931000003.tif58169
[0092] As shown in Table 2 and Figure 2, Comparative Example 3, which does not contain sugars, has an ESR that is more than three times higher than the initial ESR in an environment of 150°C. Even Comparative Example 4, which contains sorbitol, a non-reducing sugar that does not hydrolyze, has an ESR that is more than three times higher than the initial ESR in an environment of 150°C. In contrast, Examples 3 to 10, which contain reducing sugars or hydrolyzable non-reducing sugars, have ESRs that are within the range of 1.2 to 1.7 times higher than the initial ESR even after long periods of exposure to an environment of 150°C.
[0093] In this way, after the solid electrolyte layer formation process of forming a solid electrolyte layer containing a conductive polymer and the impregnation process of impregnating an electrolyte solution containing reducing sugar or hydrolyzable non-reducing sugar, it was confirmed that the increase in ESR of the solid electrolytic capacitor can be suppressed by heating the capacitor element until the reducing sugar or hydrolyzable non-reducing sugar contained in the electrolyte solution decomposes.
Claims
1. a solid electrolyte layer forming step of forming a solid electrolyte layer containing a conductive polymer between an anode body having a dielectric film and a cathode body; an impregnation step of impregnating a capacitor element having the anode body, the cathode body, and the solid electrolyte layer with an electrolyte solution containing a reducing sugar or a hydrolyzable non-reducing sugar; After the impregnation step, a heating step of heating the electrolyte until reducing sugar or hydrolyzable non-reducing sugar contained in the electrolyte is decomposed; containing, A method for producing a solid electrolytic capacitor comprising the steps of:
2. a solid electrolyte layer forming step of forming a solid electrolyte layer containing a conductive polymer and a reducing sugar or a hydrolyzable non-reducing sugar between an anode body having a dielectric film and a cathode body; a heating step of heating the solid electrolyte layer until reducing sugar or hydrolyzable non-reducing sugar contained in the solid electrolyte layer is decomposed after the solid electrolyte layer forming step; containing, A method for producing a solid electrolytic capacitor comprising the steps of:
3. the heating step is a period during which the solid electrolytic capacitor mounted on a circuit and in use is exposed to a high-temperature environment or generates heat; 3. The method for producing a solid electrolytic capacitor according to claim 1 or 2,
4. The reducing sugar or hydrolyzable non-reducing sugar is one or more selected from the group consisting of maltose, lactose, isomaltulose, melibiose, raffinose and melezitose; 3. The method for producing a solid electrolytic capacitor according to claim 1 or 2,
5. an anode body having a dielectric coating; A cathode body facing the anode body; a solid electrolyte layer interposed between the anode body and the cathode body and including a conductive polymer, or an electrolyte layer including both the solid electrolyte layer and an electrolytic solution; A reducing sugar or a hydrolyzable non-reducing sugar contained in the electrolyte layer; To have A solid electrolytic capacitor characterized by:
6. The reducing sugar or hydrolyzable non-reducing sugar is one or more selected from the group consisting of maltose, lactose, isomaltulose, melibiose, raffinose and melezitose; 6. The solid electrolytic capacitor according to claim 5,
7. an anode body having a dielectric coating; A cathode body facing the anode body; a solid electrolyte layer interposed between the anode body and the cathode body and including a conductive polymer, or an electrolyte layer including both the solid electrolyte layer and an electrolytic solution; A decomposition product derived from reducing sugar or hydrolyzable non-reducing sugar contained in the electrolyte layer; To have A solid electrolytic capacitor characterized by:
Citation Information
Patent Citations
Solid electrolytic capacitor
JP2011060980A
Power storage device
JP2015228424A